Immune memory reactivation and T cell dynamics following 12-month homologous CoronaVac booster: a longitudinal cohort study - Song, Xinran; Chen, Weixin; Bai, Shuang; Lv, Min; Wang, Jian; Zhang, Ao; Wu, Jiang; Zhao, Wei (Frontiers in Immunology, 2025)
BackgroundInactivated COVID-19 vaccines exhibit more rapid declines in antibody levels than other vaccine platforms, likely owing to transient antigen exposure and limited germinal center persistence. Moreover, although homologous boosting effectively restores humoral immunity, concerns persist regarding potential T cell exhaustion with repeated antigen exposure. We evaluated the effectiveness of delayed homologous CoronaVac booster immunization in reactivating immune memory.MethodsA prospective longitudinal cohort study was conducted with 83 healthy adults who received two CoronaVac vaccine doses (14-day interval) and a homologous booster shot after 12 months. Peripheral blood samples were collected 0, 3, 7, 10, and 14 days after booster vaccination. Neutralizing antibodies were analysed using live-virus microneutralization assays. Anti-receptor-binding domain immunoglobulin subclasses (IgG1, IgG2, IgG3, IgG4) were detected using enzyme-linked immunosorbent assay. Cytokine secretion (interferon [IFN]-γ/interleukin [IL]-2/IL-4/IL-5) was assessed using enzyme-linked immunospot assay. T cell polarization and exhaustion markers (T-bet/GATA3 and CD69/CTLA-4/PD-1) were evaluated using flow cytometry.ResultsThe geometric mean titer of neutralizing antibodies reached 254.5 on day 14. The initial immune response was dominated by IgG3, which subsequently shifted to IgG1. A significant Th1-type cellular immune response was characterized by increased IFN-γ and IL-2 secretion, and upregulated T-bet expression. Transient CD69+ T cell activation occurred between days 3 and 10 without sustained PD-1 and CTLA-4 elevation.ConclusionsDelayed homologous CoronaVac booster immunization effectively reactivates immune memory, facilitated by Th1 polarization and transient T cell activation, which do not result in T cell exhaustion. These findings suggest the potential application of long-interval immunization strategies against COVID-19.